International Survey on Extracorporeal Membrane Oxygenation Transport. Issue 2 (February 2020) - Broman, Lars Mikael; Dirnberger, Daniel R.; Malfertheiner, Maximilian V.; Aokage, Toshiyuki; Morberg, Pål; Næsheim, Torvind; Pappalardo, Federico; Di Nardo, Matteo; Preston, Tom; Burrell, Aidan J.C.; Daly, Ivonne; Harvey, Chris; et al.
Abstract : Extracorporeal membrane oxygenation (ECMO) is a lifesaving therapy for severe respiratory and circulatory failure. It is best performed in high-volume centers to optimize resource utilization and outcomes. Regionalization of ECMO might require the implementation of therapy before and during transfer to the high-volume center. The aim of this international survey was to describe the manner in which interhospital ECMO transport care is organized at experienced centers. Fifteen mobile ECMO centers from nine countries participated in this survey. Seven (47%) of them operated under the "Hub-and-Spoke" model. Transport team composition varies from three to nine members, with at least one ECMO specialist (i.e., nurse or perfusionist) participating in all centers, although intensivists and surgeons were present in 69% and 50% of the teams, respectively. All centers responded that the final decision to initiate ECMO is multidisciplinary and made bedside at the referring hospital. Most centers (75%) have a quality control system; all teams practice simulation and water drills. Considering the variability in ECMO transport teams among experienced centers, continuous education, training and quality control within each organization itself are necessary to avoid adverse events and maintain a low mortality rate. A specific international ECMO Transport platform to share data, benchmark outcomes, promote standardization, and provide quality control is required. Abstract : Supplemental Digital Content is available in the text.